Dampak Penggunaan Social Media secara Berlebihan terhadap Regulasi Diri Anak - Putri, Weni Tria Anugrah (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
Social media users today are not just limited to adults, but also young children. There are various impacts of its use, one of them on self regulation. At the age of 3 to 5 children should be able to adapt in the social environment, with the help of self-regulation. The fact that excessive use of social media in early childhood can disrupt self-regulation and result in general developmental problems, and socio-emotional development in particular. In self-regulation of early childhood, children try to be accepted in the social environment of peers. To be accepted in the social environment, children perform various ways one of them is (1) self-observation, (2) self-evaluation, (3) self-reactions. Different facts for children who experience social media addiction, children do not have self-regulation as well as the typical child before. One that is visible is, the child is seen not responding to the presence of people around him when engrossed with his social media. Social media in smartphones or other gadgets will disrupt the childs self-regulation that affects the development problem, which is one of them socio-emotional. This paper is a conceptual study of the negative impacts of social media use on the self-regulatory process of early childhood.